Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) pada Unit Kerja Pengadaan Barang dan Jasa (UKPBJ) Sekretariat Daerah Kabupaten Lanny Jaya - Marsyel Julez Ririhena; Agus Priyanto; Hiskia C.M Sapioper (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of organizational commitment (X1) and job satisfaction (X2) on OCB (Y). This research adopted quantitative methods with a descriptive approach—data collected through questionnaire distribution techniques. Data analysis techniques prioritize numerical analysis, from data preparation and tabulation to the hypothesis testing stage. Through linear regression analysis techniques, the results obtained show that if organizational commitment (X1) and job satisfaction (X2) increase, OCB (Y) also increases. The results of testing the coefficient of determination (R2) also show that OCB (Y) is influenced by organizational commitment (X1). And Job satisfaction (X2) is 95%. In comparison, the remaining 5% is influenced by other variables outside this research. At the same time, the correlation test proves that there is a powerful influence between organizational commitment (X1) and job satisfaction (X2) for OCB (Y). This evidence is also in line with the results of the t-test, where there is a partial influence of Organizational Commitment (X1) and Job Satisfaction (X2) on OCB (Y). Then, the f-test shows the simultaneous influence of Organizational Commitment (X1) and Job Satisfaction (X2) on OCB (Y). In conclusion, there is an influence of organizational commitment and job satisfaction on organizational citizenship behavior (OCB) in the goods and services procurement work unit (UKPBJ) of the regional secretariat of the Lanny Jaya district Keywords: Job satisfaction, organizational commitment, OCB